A Bis(phosphine)-Modified Peptide Ligand for Stable and Luminescent Quantum Dots in Aqueous Media - Jung, Michael E.; Trzoss, Michael; Tsay, James M.; Weiss, Shimon (Synthesis, 2013)
We describe a new class of ligands for semiconductor nanoparticles (quantum dots = QDs), which bind well and allow for their facile dissolution in aqueous solution. As a proof of principle, we have designed and synthesized a novel bis(phosphine)-modified peptide (BPMP) and shown that it has the ability to solubilize quantum dots in aqueous media. We further showed that the corresponding phosphine oxide derivatives of these new ligands are less good at solubilizing the quantum dots. These new bis(phosphine)-modified peptide ligands are easy to prepare and may well replace thiol-containing binding sequences in functionalized peptides for quantum dot coating, potentially resulting in quantum dots with higher quantum yields.
Keywords: bis(phosphine)-modified peptides; nanoparticles; quantum dots; quantum dot stabilization; ligands